LEGAL RESPONSIBILITIES OF THE LOCAL GOVERNMENT TO REDUCE THE ADDITIONAL INCOME OF EMPLOYEES OF THE CIVIL SERVANT FOR HEALTH PROFESSIONALS - Handayani, Baiq Yulia; Asmuni; Zamroni, Mohammad; Nugraheni, Ninis (JILPR Journal Indonesia Law and Policy Review, 2023)
The main objective of this study is to analyze the legal consequences of reducing the provision of additional income for health workers and to analyze the legal responsibility of local governments for reducing the right to provide additional income for health workers. The method used in this study is a normative juridical research method, so the approach taken in this research is a statutory approach (statute approach), historical approach (historical approach) and conceptual approach (conceptual approach). The results of the findings and studies in this study, it can be concluded that the legal consequences that occur if the actions taken by the local government to reduce the provision of additional income for Health Workforce Employees if they cannot be accounted for are revocable and invalid. So that the decision issued in February 2022 may be canceled, so that the Regent's regulation Number 1 of 2022 is reinstated. The legal responsibility of the local government regarding the reduction of the right to provide additional income for health workers is to return to the legal basis for providing additional income for employees based on government regulations number 12 of 2019 by looking at the principles of providing additional employee income which include the principles of justice, welfare and having legal certainty.